No Longer "Confined to the Lower Keys of Florida": Mainland United States Cultivation of Breadfruit (Artocarpus altilis) in a Changing Climate. (7th February 2023) - Fielding, Russell; Zaldivar, Jorge Julian
Abstract : Breadfruit ( Artocarpus altilis ) is a domesticated tree crop found throughout the insular Pacific and in other tropical regions of the world where it has been introduced, most notably in the Caribbean. Although breadfruit thrives in Hawai'i, as it has since before European contact, efforts to introduce breadfruit to the mainland United States have been challenged by the tree's intolerance for even mildly cold temperatures. Historically, only extreme southern Florida has been consistently warm enough to support breadfruit cultivation. Today, however, likely owing to warming temperatures associated with global climate change, but possibly also the selection of breadfruit varieties with improved cold tolerance, an increasing number of growers based throughout Florida are finding success cultivating breadfruit trees and producing fruit. Using a mixed-methods approach including interviews and surveys among forty-three Florida-based breadfruit growers, this article investigates the current status and geographical range of breadfruit in the mainland United States and considers both the sustainability implications and the remaining environmental challenges regarding its cultivation.